VD_FINDINFO Jug / 2019 / 404 vom 29. April 2019 - VD Tribunal cantonal (2019)
RÉSILIATION IMMÉDIATE, ANNULABILITÉ, DOLVICE DU CONSENTEMENT, VICE DU CONSENTEMENT, CRAINTE FONDÉE, ERREUR | 23 CO, 24 CO, 28 CO, 29 CO, 30 CO, 31 CO, 61 LPers-VD